Ett nationellt metasystem för utbildning och fostran i Tornedalen - Lars Elenius (Nordic Journal of Educational History, 2014)
A national metasystem for education and fostering in Tornedalen A national interacting metasystem of national education and fostering developed in the Finnish speaking region Tornedalen in northern Sweden from the late 19th century to the 1950s. It was not formally agreed as a deliberate education system, but was more of a tacit understanding of a common nationalistic goal within different educational institutions such as primary schools, the residential industrial schools [arbetsstugor], the folk high-schools and the different forms of explicit military education. The aim was to help the poor region economically, to spread the Swedish language and culture in the area, to break the isolation of the region through education and to integrate this geopolitically sensitive border region into the nation. The integrative phase of Swedish nationalism was a common denominator. Leading persons in the educational and fostering activities were many times the same persons. There was a consensus over party lines about the need of acculturation and assimilation of the Tornedalians. The school, the nation and the family was regarded as central concepts in the fostering of the minority into Swedish citizens. By regarding the educations in Tornealen as a metasystem of ideological influences you get an imagination of the ideological power single educations gets when interconnected as a system.